2012
DOI: 10.1155/2012/381834
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Response of Torsionally Coupled System with Magnetorheological Dampers

Abstract: The seismic response of linearly elastic, idealized single-storey, one-way asymmetric building with semiactive magnetorheological (MR) dampers with clipped-optimal algorithm is investigated. The response is obtained by numerically solving the governing equations of motion. The effects of eccentricity ratio, uncoupled time period, and ratio of uncoupled torsional to lateral frequency are investigated on peak responses which include lateral, torsional and edge displacements and their acceleration counter parts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In the squeeze mode, the MR fluid is made to flow between two plates that are perpendicular to each other and in mobile state. This is applied in impact dampers and low amplitude vibration but more dynamic forces [11][12][13][14][15].…”
Section: Modes Of Mr Fluidmentioning
confidence: 99%
“…In the squeeze mode, the MR fluid is made to flow between two plates that are perpendicular to each other and in mobile state. This is applied in impact dampers and low amplitude vibration but more dynamic forces [11][12][13][14][15].…”
Section: Modes Of Mr Fluidmentioning
confidence: 99%
“…Shook et al (2009) investigated the performance of MR dampers’ semi-active control system using a fuzzy logic controller to control the torsional response of a three-storey structure with asymmetric distribution of mass in the plan. Mevada and Jangid (2012a) investigated the performance of MR dampers’ semi-active control system via the clipped-optimal control algorithm with H 2 /LQG control strategy in controlling single-storey structure with asymmetric distribution of stiffness. Bharti et al (2014) evaluated the MR dampers’ performance in controlling the torsional response of a one-storey structure with asymmetric distribution of stiffness and investigated the influence of the building parameters and also applied voltage to the dampers on the performance of the control system.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that for torsionally flexible and strongly coupled systems, the effects of torsional coupling are more pronounced as compared to torsionally stiff systems. Mevada and Jangid (2012c) studied the effects of torsional coupling for asymmetric building installed with semi-active MR dampers and found that the effects of torsional coupling on effectiveness of semi-active MR damper system are more sensitive to the variation of eccentricity and torsional to lateral frequency ratio. Although, above studies reflect the effectiveness of passive and some of the semiactive systems in controlling the lateral-torsional responses, however, no specific study has been done to investigate the effectiveness of semi-active stiffness dampers for asymmetric buildings.…”
Section: Introductionmentioning
confidence: 99%